THEORETICAL FOUNDATIONS FOR REDUCING THE SHADOW ECONOMY IN THE REPUBLIC OF UZBEKISTAN USING FINANCIAL RESOURCES (International Conference on Economics, Finance, Banking and Management, 2025)
In recent years, this article in our republic examines the issues of the effective use of financial instruments to reduce the share of the shadow economy in the country, as well as the fact that the work of tax authorities to combat the widespread practice of concealing the amount of income by taxpayers and the use of tax evasion schemes , are not carried out separately and consistently, led to a decrease in tax discipline, a hidden study was conducted to analyze and evaluate the results of maintaining the scale of the economy and the deterioration of business conditions for honest entrepreneurs, and scientific and practical conclusions and proposals were developed for its application.